The Implementation of the Think-Pair-Share Technique to Improve Students' Reading Comprehension - Anni Nurul Hidayati; Ririn Dwi Kartikasari (Yayasan Cerdas Pedia Indonesia, 2026)
Reading comprehension instruction globally and in Indonesia frequently suffers from passive, teacher-dominated paradigms, resulting in alarmingly low student proficiency. This research systematically employed a Classroom Action Research design across three iterative cycles to investigate the Think-Pair-Share technique's direct impact on eleventh-grade students' comprehensive understanding of complex hortatory exposition texts at MAN Klaten. Mixed-methods data, explicitly including standardized test scores alongside structured qualitative observation rubrics, were rigorously collected and comprehensively analyzed. The findings unequivocally revealed that this structural implementation significantly enhanced cognitive proficiency, escalating the mean reading score from 52.73 to 84.55 while drastically reducing overall score dispersion. Furthermore, students exhibited elevated academic confidence and highly equitable participation during active peer-mediated negotiations. Replacing traditional instructional models with this collaborative technique successfully mandates individual cognitive accountability and fundamentally democratizes classroom dynamics, providing a robust empirical blueprint for global educators to actively foster independent, lifelong reading literacy within modern educational learning environments effectively.